PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK BERBASIS APLIKASI ANDROID PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Noor Mayaminiy Maulidah; Lailatul Mubarokah; Achmad Dhany Fachrudin (LPPM STKIP PGRI Sidoarjo, 2021)
The development of android-based comical learning media is motivated by the number of students who find it difficult to achieve complete learning on the material for the Two Variable Linear Equation System (SPLDV). It is known that based on the field analysis, one of the reasons is that a lot of time is wasted to understanding the problem, making mathematical models and than solving them. The purpose of this research is to develop learning media that is attractive, easy to use and can improve the students learning outcomes, especially in class grade eight. Because many students are already using Android as technology develops, the teaching media developed is based on Android. It also supports the implementation of Distance Learning (PJJ) during the pandemic. The concept of learning media is the delivery of material in the form of comics that are adjusted to the order of completion of each step. This research is aimed at eighth grade students. This research used 10 stages of the development model, according to Sugiyono (2012). And for the criteria for the quality of learning media using three criteria according to Nieveen (1999). The presentation and suitability between the material and the media is considered with validity with an average score of 3.43. it is very practical, so it is easy to use by students and teachers with an average score of 3.42. Based on the results of the study, it was found that the effective value media was used by students with an average score of 3.17 student responses, and an average score of 74.7 student learning outcomes tests, with a KKM of 70. So it can be deduced that the learning media developed fulfills the criteria.